Preparation method of SnO2 electron transport layer modified by potassium trifluoromethanesulfonate and preparation method of positive perovskite solar cell

The SnO2 electron transport layer is modified by potassium trifluoromethanesulfonate, which solves the problem of many surface defects in SnO2 and improves the photoelectric conversion efficiency and stability of perovskite solar cells.

CN119894337APending Publication Date: 2025-04-25BEIJING UNIV OF TECH

Patent Information

Application Number
CN202510301074.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Due to the poor crystallinity and many surface defects of the SnO2 electron transport layer, the photoelectric conversion efficiency of perovskite solar cells is low.

Method used

By modifying the SnO2 electron transport layer with potassium trifluoromethanesulfonate, oxygen vacancies and hydroxyl defects on the surface of SnO2 are reduced, thereby improving the quality of the electron transport layer.

Benefits of technology

The open circuit voltage and photoelectric conversion efficiency of perovskite solar cells are improved, and the stability of the cells is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005311532560000061
    Figure BDA0005311532560000061
  • Figure HDA0005311532690000011
    Figure HDA0005311532690000011
  • Figure HDA0005311532690000012
    Figure HDA0005311532690000012
Patent Text Reader

Abstract

The invention discloses a preparation method of a SnO2 electron transport layer modified by potassium trifluoromethanesulfonate and a positive perovskite solar cell, and belongs to the technical field of perovskite solar cell preparation. The preparation method of the potassium trifluoromethanesulfonate modified electron transport layer comprises the following steps: mixing urea, concentrated hydrochloric acid, mercaptoacetic acid, stannous chloride dehydrate, potassium trifluoromethanesulfonate and deionized water to form a chemical bath solution; soaking the conductive glass substrate in the chemical bath solution for deposition reaction; and cleaning and annealing the conductive glass substrate to form SnO2 modified by potassium trifluoromethanesulfonate. And sequentially preparing a perovskite light absorption layer, a hole transport layer, a modification layer and a metal electrode on SnO2 to obtain the positive perovskite solar cell. According to the invention, SnO2 modified by potassium trifluoromethanesulfonate is used as an electron transport layer, so that defects such as hydroxyl groups on the surface of SnO2 are reduced, carrier extraction is promoted, and the open-circuit voltage and photoelectric conversion efficiency of the cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite solar cell preparation, and in particular relates to a method for preparing a SnO2 electron transport layer modified by potassium trifluoromethanesulfonate and a positive perovskite solar cell. Background Art

[0002] As one of the functional layers of perovskite solar cells, the electron transport layer has the functions of electron extraction and transmission, which is crucial to the photoelectric conversion efficiency and stability of solar cells. Tin dioxide (SnO2) has the advantages of large optical band gap, high optical transmittance, high mobility, excellent chemical stability and easy low-temperature preparation, and is widely used as the electron transport layer of perovskite solar cells.

[0003] The SnO2 electron transport layer prepared by chemical bath deposition has the advantages of simple manufacturing process, excellent film uniformity and large-area preparation, and has received widespread attention. Chemical bath deposition is a method based on solution-based film growth. There are many variables in the growth process. HCl volatilization, precipitate formation and concentration changes will affect the quality of SnO2 film. In addition, the SnO2 surface prepared by chemical bath deposition often has a large number of defects such as oxygen vacancies and hydroxyl groups. These defects will become carrier capture sites, hindering the transport of carriers in the battery, thereby reducing the efficiency and stability of the battery. Therefore, improving the chemical bath deposition method and reducing SnO2 surface defects are crucial to improving the performance of perovskite solar cells. Summary of the invention

[0004] In view of the problem that the photoelectric conversion efficiency of perovskite solar cells is low due to poor crystallinity and more surface defects of the SnO2 electron transport layer, the present invention provides a method for preparing a SnO2 electron transport layer modified with potassium trifluoromethanesulfonate and a positive perovskite solar cell to overcome the above-mentioned shortcomings.

[0005] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions:

[0006] In a first aspect, the present invention first provides a method for preparing a SnO2 electron transport layer modified by potassium trifluoromethanesulfonate, comprising the following steps:

[0007] Step 1: Prepare a clean conductive glass substrate;

[0008] Step 2: Mix urea, stannous chloride dihydrate (SnCl2·2H2O), thioglycolic acid, hydrochloric acid, potassium trifluoromethanesulfonate and deionized water to form a SnO2 chemical bath solution;

[0009] Step 3: Soak the clean conductive glass substrate in a chemical bath solution and place it in an oven for deposition reaction;

[0010] Step 4: After the reaction is completed, the conductive glass substrate is cleaned and annealed to form a SnO2 electron transport layer on the conductive glass substrate.

[0011] Preferably, in the step 2, urea, SnCl2·2H2O, potassium trifluoromethanesulfonate, thioglycolic acid, hydrochloric acid (37wt%) and deionized water are first mixed into a stock solution in a ratio of 1g:220mg:(7-30)mg:20μL:1mL:80mL, and then the stock solution is diluted with deionized water in a ratio of 1:3-1:5 to form a chemical bath solution.

[0012] Preferably, in step three, the oven temperature is 90-120° C., and the deposition reaction time is 50-120 min.

[0013] Preferably, the cleaning treatment in step 4 is to soak in deionized water and isopropanol and ultrasonically clean for 10 to 20 minutes respectively, and then blow dry with nitrogen.

[0014] Preferably, the annealing temperature in step 4 is 100-200° C., and the annealing time is 30-60 min.

[0015] In a second aspect, the present invention also provides the use of a SnO2 electron transport layer modified with potassium trifluoromethanesulfonate prepared by any of the methods described above in a positive-type perovskite solar cell.

[0016] In a third aspect, the present invention further provides a method for preparing a positive-structure perovskite solar cell, comprising the following steps:

[0017] Step 1: Prepare a clean conductive glass substrate;

[0018] Step 2: preparing an electron transport layer on the surface of the conductive glass substrate according to the method described above;

[0019] Step 3: coating the lead iodide solution and the organic salt solution on the surface of the electron transport layer in sequence to form a perovskite light absorbing layer;

[0020] Step 4: preparing a hole transport layer on the surface of the perovskite light absorbing layer;

[0021] Step 5: sequentially prepare a modification layer and a metal electrode on the surface of the hole transport layer to obtain the perovskite solar cell.

[0022] Preferably, steps 3 to 5 are all completed in a glove box with a nitrogen atmosphere to isolate the device from the influence of the external environment.

[0023] Preferably, the lead iodide solution comprises a solution of lead iodide dissolved in a mixture of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), and the organic salt solution comprises a solution of formamidine hydroiodide (FAI) and methylammonium chloride (MACl) dissolved in isopropyl alcohol (IPA).

[0024] Furthermore, in the lead iodide solution, each 1 mL of a mixed solution of DMF and DMSO (the volume ratio of DMF and DMSO is 9:1) corresponds to 692 mg of lead iodide; and in the organic salt solution, each 1 mL of IPA solution corresponds to 90 mg of FAI and 18 mg of MACl.

[0025] Furthermore, the spin coating speed of the lead iodide is 1500 r / min, and the spin coating time is 30 s; the spin coating speed of the organic salt is 2000 r / min, and the spin coating time is 30 s.

[0026] Furthermore, after the lead iodide solution is spin-coated, it is necessary to anneal at 70° C. for 1.5 min. After the organic salt solution is spin-coated, the sample needs to be transferred to the air, the air humidity is maintained at 35% RH, and the sample is annealed at 150° C. for 15 min. After the annealing is completed, the sample is transferred to a glove box.

[0027] Furthermore, the material of the hole transport layer is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), and 72.3 mg of Spiro-OMeTAD powder is weighed and dissolved in 1 mL of chlorobenzene solution to obtain a hole transport layer solution.

[0028] Furthermore, the hole transport layer solution is spin-coated at a speed of 3000 r / min and a spin-coating time of 30 s.

[0029] Furthermore, the modification layer material is molybdenum trioxide (MoO3), the thickness of the modification layer is 2 to 4 nm, the metal electrode is a silver electrode, the thickness of the metal electrode is 90 to 120 nm, and both the modification layer and the metal electrode are prepared by thermal evaporation.

[0030] The obtained positive perovskite solar cell with potassium trifluoromethanesulfonate-modified SnO2 as the electron transport layer has a hierarchical structure from bottom to top: conductive glass substrate, potassium trifluoromethanesulfonate-modified SnO2 electron transport layer, FA x MA 1- x PbI3 perovskite light absorption layer, Spiro-OMeTAD hole transport layer, MoO3 modification layer and metal Ag electrode.

[0031] Beneficial Effects

[0032] The present invention uses potassium trifluoromethanesulfonate as an additive for SnO2, which reduces oxygen vacancies and hydroxyl defects on the surface of SnO2, inhibits non-radiative recombination of carriers, promotes the extraction and transmission of carriers by the electron transport layer, and thus improves the open circuit voltage and photoelectric conversion efficiency of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Flow chart of the preparation of SnO2 electron transport layer in Example 1 of the present invention.

[0034] Figure 2 The current density-voltage (JV) curves of the examples and comparative examples provided according to the present invention are shown in FIG. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0036] Example 1

[0037] A positive perovskite solar cell based on a SnO2 electron transport layer modified by potassium trifluoromethanesulfonate, the preparation process of which is as follows:

[0038] Step 1: Prepare a clean ITO conductive glass substrate:

[0039] Step 2: Prepare SnO2 chemical bath solution modified with potassium trifluoromethanesulfonate:

[0040] First, urea, SnCl2·2H2O, potassium trifluoromethanesulfonate, thioglycolic acid, hydrochloric acid (37 wt%) and deionized water were mixed in a ratio of 1 g: 220 mg: 15 mg: 20 μL: 1 mL: 80 mL to form a stock solution, and then the stock solution was diluted with deionized water in a ratio of 1:5 to form a chemical bath solution.

[0041] Step 3: Preparation of SnO2 electron transport layer modified by potassium trifluoromethanesulfonate:

[0042] The clean conductive glass substrate was immersed in the chemical bath solution and placed in an oven for deposition reaction. The oven temperature was set to 90°C and the reaction time was 60 minutes. After the reaction was completed, the conductive glass substrate was taken out and soaked in deionized water and isopropanol and ultrasonically cleaned for 10 minutes. The cleaned substrate was then taken out, dried with nitrogen, and annealed on a hot plate at 150°C for 40 minutes to obtain a SnO2 electron transport layer modified with potassium trifluoromethanesulfonate. The sample was transferred to a glove box for subsequent operations.

[0043] Step 4: Prepare a perovskite layer on the electron transport layer:

[0044] Weigh 692 mg of lead iodide (PbI2), dissolve it in 1 mL of a mixed solution of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (the volume ratio of DMF to DMSO is 9:1), and stir it at 70°C for 1 hour to obtain a transparent lead iodide solution; weigh 90 mg of formamidinium iodide (FAI) and 18 mg of methylammonium chloride (MACl), dissolve them in 1 mL of isopropanol (IPA) solution, and stir them for 1 hour to form an organic salt solution; take 30 μL of the lead iodide solution and drop it on tin oxide, spin coat it at a speed of 1500 r / min for 30 seconds, and anneal it at a temperature of 70°C for 1.5 minutes after the spin coating; take 50 μL of the organic salt solution and drop it on the lead iodide, spin coat it at a speed of 2000 r / min for 30 seconds, transfer it to the air after the spin coating, and anneal it at a temperature of 150°C for 15 minutes, and control the air humidity to 35% RH during the annealing.

[0045] Step 5: Prepare a hole transport layer, a MoO3 modified layer and a metal Ag electrode on the perovskite layer:

[0046] 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) powder was weighed and dissolved in 1 mL of chlorobenzene solution. The perovskite was transferred to a glove box and cooled to room temperature. 40 μL of Spiro-OMeTAD solution was dropped on the perovskite layer and spin-coated at 3000 r / min for 30 s. The sample was then transferred to a thermal evaporation device and a 3 nm MoO3 modification layer and a 100 nm metal Ag electrode were sequentially evaporated at an evaporation pressure of 1×10 -5 Pa.

[0047] At this point, a positive perovskite solar cell based on a SnO2 electron transport layer modified with potassium trifluoromethanesulfonate was obtained.

[0048] Example 2

[0049] The positive perovskite solar cell prepared according to the steps of Example 1 is different from Example 1 in that urea, SnCl2·2H2O, potassium trifluoromethanesulfonate, thioglycolic acid, hydrochloric acid (37wt%) and deionized water are mixed in a ratio of 1g:220mg:30mg:20μL:1mL:80mL; the other steps remain unchanged.

[0050] Comparative Example

[0051] The positive perovskite solar cell prepared according to the steps of Example 1 is different from Example 1 only in that the SnO2 chemical bath solution does not contain potassium trifluoromethanesulfonate, and the other steps remain unchanged.

[0052] The solar cell performances of the above embodiments and comparative examples are compared below:

[0053] Figure 2 The JV curves of the embodiments and comparative examples provided by the present invention, and the corresponding battery performance parameters are listed in Table 1:

[0054] Table 1. Photoelectric performance parameters of positive perovskite solar cells based on different electron transport layers

[0055]

[0056] from Figure 2 As can be seen from Table 1, compared with the comparative example, the open circuit voltage V OC , fill factor FF and photoelectric conversion efficiency PCE have been significantly improved. Potassium trifluoromethanesulfonate modified SnO2, which reduced the defects such as oxygen vacancies and hydroxyl groups on the SnO2 surface, promoted the transmission of carriers, reduced the recombination of carriers, and thus improved the open circuit voltage and photoelectric conversion efficiency of perovskite solar cells.

[0057] At this point, a potassium trifluoromethanesulfonate-modified SnO2 electron transport layer and its preparation method in positive-type perovskite solar cells have been introduced.

[0058] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a SnO2 electron transport layer modified by potassium trifluoromethanesulfonate, characterized in that: The following steps are involved: Step 1: Mix urea, stannous chloride dihydrate (SnCl2·2H2O), thioglycolic acid, hydrochloric acid, potassium trifluoromethanesulfonate and deionized water to form a potassium trifluoromethanesulfonate-modified SnO2 chemical bath solution; Step 2: Soak the clean conductive glass substrate in a chemical bath solution and place it in an oven for deposition reaction; Step 3: After the reaction is completed, the conductive glass substrate is cleaned and annealed, so that a SnO2 electron transport layer is formed on the conductive glass substrate.

2. The method according to claim 1, characterized in that In the step 1, urea, SnCl2·2H2O, potassium trifluoromethanesulfonate, thioglycolic acid, hydrochloric acid (37wt%) and deionized water are first mixed into a stock solution in a ratio of 1g:220mg:(7-30)mg:20μL:1mL:80mL, and then the stock solution is diluted with ionized water in a ratio of 1:3-1:5 to form a chemical bath solution.

3. The method according to claim 1, characterized in that In the step 2, a deposition reaction is carried out, the oven temperature is 90 to 120° C., and the deposition time is 50 to 120 minutes.

4. The method according to claim 1, characterized in that The cleaning treatment in step 3 is to soak in deionized water and isopropanol and ultrasonically clean for 10 to 20 minutes respectively, and then blow dry with nitrogen.

5. The method according to claim 1, characterized in that In the step three, the annealing temperature is 100-200° C., and the annealing time is 30-60 min.

6. A SnO2 electron transport layer modified with potassium trifluoromethanesulfonate prepared according to the method described in any one of claims 1 to 5.

7. A method for preparing a positive structure perovskite solar cell, characterized in that: The following steps are involved: -Prepare a clean conductive glass substrate; -Preparing an electron transport layer on the surface of a conductive glass substrate according to the method of claims 1 to 5; -Preparation of FA on the surface of electron transport layer x MA 1-x PbI3 perovskite light absorbing layer; -Prepare the Spiro-OMeTAD hole transport layer on the surface of the perovskite light absorbing layer; -Prepare a MoO3 modified layer and a metal Ag electrode on the surface of the hole transport layer in sequence to obtain the positive structure perovskite solar cell.

Citation Information

Patent Citations

  • Preparation method of perovskite solar cell

    CN114639785A

  • Perovskite solar cell electron transport layer modified by chlorine-containing organic potassium salt, perovskite solar cell and preparation method of perovskite solar cell

    CN114843405A

  • Phosphorus-containing flame retardant modified perovskite solar cell and preparation method thereof

    CN116887603A

  • Perovskite solar cell with lithium trifluoromethanesulfonate modified tin oxide as electron transport layer and preparation method thereof

    CN117956815A

Cited By

  • Perovskite solar cell and preparation method thereof

    CN120981078A